Ferris Bueller's day off [videorecording (Blu-Ray)] - Newborn, Ira (Paramount Home Entertainment, 2009)
Ferris Bueller has played hooky a number of times. But this time he has the entire school and more believing he is on the verge of death. On this special day off, Ferris invites his friend Cameron and girlfriend Sloane to join him in his day of fun. Ferris talks Cameron into borrowing his father's precious Ferrari for the day's transportation. All the while, Principal Ed Rooney is determined to prove Ferris is faking his illness. Jeanie is Ferris's agitated sister who also wants to catch Ferris in his lie. Ferris enjoys his day with his friends, until they notice that the mileage of the Ferrari reads too many miles, sending Cameron to suffer his own blow out.